Experimental verification of biomechanical model of bipedal walking to simulate vertical loads induced by humans. (15th March 2022) - Ruiz, Dianelys Vega; Magluta, Carlos; Roitman, Ney
Abstract: A set of empirical equations to estimate parameters and initial conditions for a biomechanical bipedal walking model is proposed in this study. These equations are intended to generate vertical loads induced by humans on rigid ground. Forty-five volunteers are recruited to participate in an experimental program to walk on a rigid surface covered by force plates, in which the walking forces are measured. The bipedal model is adjusted to fit the vertical ground reaction forces (GRFs) measured experimentally. Multiple simulations are carried out within ranges of input parameters to achieve the best correlations possible between the model's predictions and measured data. Based on empirical data, regression equations are proposed for the fundamental model's parameters and initial conditions as functions of pedestrians' mass, height, and gait speed. The proposed regression functions can produce stable gaits and GRF with a typical M-shape profile in a certain range of walking speed. Furthermore, this set of regression functions was used to generate the measured GRF-time histories for comparison. To reproduce the step-by-step variations observed in recorded GRF profiles each step is modeled with a different speed. The results of this study verify the practicality of a set of equations to obtain parameters to make it possible to employ bipedal models in predicting loads induced by humans in the vertical direction. Graphical abstract: Highlights: A biomechanical bipedal model is adopted to represent a walking pedestrian. Ground reaction forces are measured in tests involving walking individuals. Multiple simulations matched the model predictions with experimental data. Regression equations are proposed for the model parameters and initial conditions. The step-by-step variability is modeled to simulate a more realistic loading.